2019
DOI: 10.1177/1179550619871274
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neck Space Infections: A Case Series and Review of the Literature

Abstract: Deep neck spaces are regions of loose connective tissue filling areas between the 3 layers of deep cervical fascia, namely, superficial, middle, and deep layers. The superficial layer is the investing layer, The pretracheal layer is the intermediate layer and the prevertebral layer is the deepest layer. Deep neck space infection (DNI) is defined as an infection in the potential spaces and actual fascial planes of the neck. Once the natural resistance of fascial planes is overcome, spread of infection occurs al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The prognosis of successful DNI treatment in patients with CKD, especially in RTRs, is worse than in general population [51]. Reoperations and longer hospitalizations are often required in these patients [53].…”
Section: Deep Neck Infections (Dnis)mentioning
confidence: 99%
“…The prognosis of successful DNI treatment in patients with CKD, especially in RTRs, is worse than in general population [51]. Reoperations and longer hospitalizations are often required in these patients [53].…”
Section: Deep Neck Infections (Dnis)mentioning
confidence: 99%
“…Many studies identified odontogenic origins to DNSIs, citing odontogenic sources in 28%, 12%, 70.6%, and 92.7% of cases. [7,11,17,21] This is common for low income countries with inappropriate equipment for basic dental care, delayed extractions, a lack of dentists, and high numbers of patients with poor oral hygiene. Contrast CT scan is the gold standard method of diagnosis for DNSIs.…”
Section: Resultsmentioning
confidence: 99%
“…[9,13] Delays in diagnosis and treatment can result in life-threatening complications, namely, airway compromise, necrotizing fasciitis, mediastinitis and sepsis. [17]…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the mentioned comorbid conditions, there are studies in the literature reporting that low socio-economic status and low educational status increase the susceptibility to the development of DNSI (12,13,14). In addition, infections caused by resistant microorganisms due to the widespread use of antibiotics also increase the risk in this population (6,15). Due to the widespread and timely use of antibiotics and the easy accessibility to broad-spectrum antibiotics, the incidence of deaths and complications due to DNSI has decreased (16).…”
Section: Discussionmentioning
confidence: 99%